AUTHENTIC LEADERSHIP PRACTICES OF EXCELLENT PRINCIPALS ON TEACHERS' WORK ENGAGEMENT IN NATIONAL SECONDARY SCHOOLS OF SOUTHERN MALAYSIA - Thilagam Gurusamy; Zuraidah Abdullah; Norazlina Ros Abd Rahman (Journal of Islamic, Social, Economics and Development, 2023)
Today's educational systems across the world confront a number of challenges in establishing and sustaining effective teaching and learning. This imposes governments around the globe making myriads of efforts to obtain a high-quality education. At the same time, it elevates the amount of work-related stress and lowers enthusiasm among teachers as policy implementers. As a consequence, research is required to determine the impact of excellent principal leadership, particularly authentic leadership on the teachers’ work engagement by educators in Malaysian secondary schools. This study used a quantitative design strategy with the utilisation of the ALQ and UWES instruments. The study sample included 298 teachers from the southern region of Malaysia who were led by excellent principals. The research data, which was analysed using IBM SPSS 26 statistical software, revealed that excellent principals' authentic leadership and teachers’ work engagement occurred at a high and very high level. Correlation analysis reveals a substantial moderate link (r =.411) between excellent principals' authentic leadership practises and teachers’ work engagement. In fact, the data show that the principal's self-awareness is the primary predictor, accounting for up to 13.6% of the variance (R²=0.136) in enhancing teachers’ work engagement. The study's findings have therefore added to current comprehension of how excellent principals' leadership practice in Malaysia affects teachers' organisational behaviour, particularly their work engagement in improving the performance of their schools.